UPAYA PENINGKATAN EFIKASI DIRI SISWA MELALUI KECERDASAN EMOSIONAL - Murni Melliani Safitri (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2023)
Self-efficacy in students can help students in carrying out the learning process at school, a student who has self-efficacy shows self-confidence in his ability to carry out his obligations and responsibilities as a student at school and feels confident in completing the tasks assigned to him. given by the teacher. In this study aiming to find out the efforts to increase students' self-efficacy through emotional intelligence, the research was conducted at MTsS Harapan Bangsa Aceh Barat, as many as 146 MTsS Harapan Bangsa Aceh Barat were used as research samples. This study uses quantitative analysis with correlational methods. The measuring instrument in this study uses an emotional intelligence scale based on Goleman's theory (2004) and a self-efficacy scale based on Bandura's theory (1997). From the research it was found that self-efficacy (self-efficacy) can be increased by the presence of emotional intelligence in students as seen from the correlation coefficient value of r = 0.675 with p = 0.000. This shows that there is a very significant positive relationship between emotional intelligence and self-efficacy. It can be said that the higher the emotional intelligence, the higher the students' self-efficacy